2023
DOI: 10.1111/cdev.14042
|View full text |Cite
|
Sign up to set email alerts
|

Children's overestimation of performance across age, task, and historical time: Ameta‐analysis

Mengtian Xia,
Astrid M. G. Poorthuis,
Sander Thomaes

Abstract: Children tend to overestimate their performance on a variety of tasks and activities. The present meta‐analysis examines the specificity of this phenomenon across age, tasks, and more than five decades of historical time (1968–2021). Self‐overestimation was operationalized as the ratio between children's prospective self‐estimates of task performance and their actual (i.e., objectively measured) task performance. A total of 246 effect sizes from 43 published articles were analyzed (4277 participants; 49.6% gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 148 publications
0
3
0
Order By: Relevance
“…These changes have been found in tasks that assess children's memory (e.g., tasks in which children are asked to estimate the number of items they will remember [1][2][3] ), motor performance (e.g., tasks in which children are asked how far they can jump or throw a ball [4][5][6] ), visual search (e.g., tasks in which children are asked to predict how many hidden objects they can find 7 ) and probabilistic reasoning tasks (e.g., tasks in which children must estimate the probability of a desirable randomly determined outcome 8,9 ; see Figure 1). These studies show that young children overestimate task performance to a greater degree than older children 10 . For example, in terms of children's motor performance, 4-year-olds overpredict how far they will jump by ~40% while 6-year-olds over-predict how far they will jump by ~20% 6 .…”
Section: Introductionmentioning
confidence: 63%
“…These changes have been found in tasks that assess children's memory (e.g., tasks in which children are asked to estimate the number of items they will remember [1][2][3] ), motor performance (e.g., tasks in which children are asked how far they can jump or throw a ball [4][5][6] ), visual search (e.g., tasks in which children are asked to predict how many hidden objects they can find 7 ) and probabilistic reasoning tasks (e.g., tasks in which children must estimate the probability of a desirable randomly determined outcome 8,9 ; see Figure 1). These studies show that young children overestimate task performance to a greater degree than older children 10 . For example, in terms of children's motor performance, 4-year-olds overpredict how far they will jump by ~40% while 6-year-olds over-predict how far they will jump by ~20% 6 .…”
Section: Introductionmentioning
confidence: 63%
“…These results indicate that during the period under observation, the participants’ mean calibration did not change significantly, with no signs of interindividual differences. Although a recent meta-analysis [ 50 ] found that children’s self-overestimation gradually decreased with age from early to late childhood, this finding was based on cross-sectional studies. In contrast, the present study’s longitudinal results show that for the age range considered here, overestimation remained relatively stable.…”
Section: Discussionmentioning
confidence: 99%
“…These results imply that during the period of the study, students' mean calibration did not change significantly with no signs of inter-individual differences. Although a recent meta-analysis [46] indicated that children's self-overestimation gradually decreases with age, from early to late childhood, this was based on cross-sectional studies. On the contrary, the present longitudinal results show that for the specific age-range, overestimation remains relatively stable.…”
Section: Discussionmentioning
confidence: 99%